1991
DOI: 10.3758/bf03335250
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned food preferences

Abstract: Animals learn to prefer the flavors of foods on the basis of the foods' postingestive nutritional consequences. This has been demonstrated with the conditioned flavor preference paradigm. With this paradigm, one flavor (the CS+) is paired with a nutrient that is orally consumed or is infused via a post-oral (e.g., intragastric) route; another flavor (CS-) is paired with a nonnutritive source. In subsequent two-choice tests, the rats displayed reliable preferences for the CS+ flavor over the CS-flavor. Very str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Thus, caloric conditioning theory states that the pleasurable state of satiety following a meal increases the preference for the taste of the food that brings about the satiety. A series of elegant studies using caloric conditioning paradigms indeed have shown that subjects learn a preference for the taste of foods which are rich in energy (carbohydrates or fat) whereas they do not learn a preference for the taste of foods that are low in energy (eg Birch, 1987Birch, , 1989Birch, , 1991Booth, 1985;Capaldi, 1996;Garcia et al, 1974;Kern et al, 1993;Rogers, 1994;Sclafani, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, caloric conditioning theory states that the pleasurable state of satiety following a meal increases the preference for the taste of the food that brings about the satiety. A series of elegant studies using caloric conditioning paradigms indeed have shown that subjects learn a preference for the taste of foods which are rich in energy (carbohydrates or fat) whereas they do not learn a preference for the taste of foods that are low in energy (eg Birch, 1987Birch, , 1989Birch, , 1991Booth, 1985;Capaldi, 1996;Garcia et al, 1974;Kern et al, 1993;Rogers, 1994;Sclafani, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Pairing a flavor with a nutrient increases subsequent preference for the flavor (Bolles, 1983;Booth, 1990;Mehiel, 1991;Sclafani, 1990Sclafani, , 1991Tordoff, 1991;Weingarten, 1990). This form of conditioning is reinforced partly by the hedonic effects of the nutrient's oral-sensory properties (flavor) and partly by the nutrient's postingestive effects (calories).…”
mentioning
confidence: 99%
“…First, Sclafani (1991) reviews several studies that show resistance to extinction in Pavlovian conditioning paradigms using food stimuli with rats. Second, Grant (1964) distinguished between Pavlovian A and Pavlovian B conditioning; in the later form the effect of the UCS is independent of instrumental acts by the organism.…”
Section: Theoretical Basis Of Ec: Is It Qualitatively Different From mentioning
confidence: 99%